Floating Concrete Opportunities for Future Sustainable Development of Floating Buildings Structures (International Journal of Innovative Research in Engineering & Management, 2022)
In India, Floating structures are deficient as  maximum construction is done on land. But due to high rate  of increasing population we need an alternative for our future  generations. It has been successfully confirmed that we can  built floating structures that can float on water. Many  structures have been constructed so far by different  countries. Floating structures like docks, floating islands,  floating supermarkets, floating terminals, airports etc. have  been constructed and are functioning successfully. In India  we are lacking the concept of floating structures which can  help us to reserve land and use water bodies for the  construction. Firstly, we need to adopt floating structures as  an alternative for the structures like airports, terminals, as  they require more land and then later, we can shift to other  types of floating structures. The main objective of our study  is to develop such a concrete that can float in water (i.e., low  density concrete) and that is possible only when the density  of our concrete is less than that of water that is less than  1000kg/m3Along with the lesser density it should fulfill the  strength requirements both compressive as well as flexural  strength. One of the most important objective of our study is  that we are using light weight aggregates like glass beads and  pumice stone as an alternative to the coarse aggregate along  with sand. We are also using Aluminium powder in order to  increase porosity of our concrete along with fly ash as fly ash  can be used as a filler to provide enough bulk and surface  area to our specimen to float. Secondly we will try to prove  that by using glass beads as an alternative to the aggregate  the property of concrete in flexure is enhancing as glass  beads are less prone to fatigue. Thirdly we will try to show  that use of glass beads as an makes it eco-friendly.
Keywords: Light Weight Floating Concrete; Glass Beads; Pumice Stones; Aluminium Powder; Fly ash; Super plasticizer (HRWRA); Sand and Cement